Synthesis of carbon nanotubefrom waste cooking oil catalysedby mill scale waste for development of flexible microstrip patch antenna - Ismail, Ismayadi; Mustaffa, Muhammad Syazwan; Abbas, Zulkifly; Hamidon, Mohd Nizar; Hasan, Intan Helina; Abdullah, Nor Hapishah (2018)
The synthesis of carbon nanotube (CNT) using waste cooking oil (WCO) as green starting material was carried out in a floating catalyst thermal vapor deposition reactor by using millscale waste which is iron oxide nanoparticles (IONP) as a catalyst. Their morphology, composition, mass of substance changes, Raman characteristics and electromagnetic (EM) wave absorption performance were measured by Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-ray (EDX), Thermal Gravimetric Analysis (TGA), RAMAN spectroscopy and Vector Network Analyzer (VNA). Results indicated that iron nanoparticles were distributed on MWCNT surface with agglomeration, and MWCNT crucially affected the magnetic properties of iron nanoparticle. Samples which contain higher content of carbon as confirmed by Raman characteristic possess higher absorption value. The enhanced EM-wave absorption performance was mainly ascribed to the increased of interfacial polarization and dielectric loss that resulting from the introduction of MWCNT. The result illustrated that the introduction of MWCNT into magnetic materials can enable the efficient design of excellent patch antenna for wireless communication application.